2020
DOI: 10.1111/nmo.14056
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of functional heartburn and reflux hypersensitivity with proven gastroesophageal reflux disease

Abstract: Heartburn is a typical symptom of gastroesophageal reflux disease (GERD). 1 In the absence of alarm symptoms, an empiric trial of a proton pump inhibitor (PPI) has high sensitivity (75%-80%), but modest specificity (40%-60%) for objective GERD evidence on endoscopy or ambulatory reflux monitoring. 2,3 Mucosal processes (including eosinophilic esophagitis) and motor disorders

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…Moreover, Yadlapati et al revealed that patients with NERD, RH and FH had similar levels of psychosocial symptom and hypervigilance scales 28 . Furthermore, Rengarajan et al demonstrated that patients with proven GERD with overlapping FH and RH undergoing ambulatory reflux monitoring on PPI therapy have identical levels of anxiety and depression compared to conventional FH and RH diagnosed off PPI therapy in unproven GERD 30 . In our cohort, levels of EHAS, both depression and anxiety are distributed similarly among GERD phenotypes.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, Yadlapati et al revealed that patients with NERD, RH and FH had similar levels of psychosocial symptom and hypervigilance scales 28 . Furthermore, Rengarajan et al demonstrated that patients with proven GERD with overlapping FH and RH undergoing ambulatory reflux monitoring on PPI therapy have identical levels of anxiety and depression compared to conventional FH and RH diagnosed off PPI therapy in unproven GERD 30 . In our cohort, levels of EHAS, both depression and anxiety are distributed similarly among GERD phenotypes.…”
Section: Discussionsupporting
confidence: 62%
“…In our cohort, levels of EHAS, both depression and anxiety are distributed similarly among GERD phenotypes. Since pathological GERD and functional disorders may overlap and coexist, 30‐32 these differences among different studies are potentially related to patients' selection with varying extents of overlapping that are difficult to confirm or demonstrate.…”
Section: Discussionmentioning
confidence: 99%
“…98 Yet others have demonstrated similar psychological profiles between functional heartburn and reflux hypersensitivity. 172 These data suggest that reflux hypersensitivity might be a heterogeneous category, but more research is needed to clarify which patients with reflux hypersensitivity require GERD management vs. neuromodulators vs. both.…”
Section: Pathophys Iologymentioning
confidence: 98%
“…Broadly, this is a focus of the Rome Foundation Overlap in DGBI working team who will aim to provide guidance on further testing and management of DGBI symptoms in patients with organic disease, including how to prioritize different treatment strategies such as when centrally versus peripherally acting treatments should be used and the use of BGBT in the context of both clinical trials and practice 28 . In the realm of esophageal disorders, a study has shown that patients with diagnoses of functional heartburn or reflux hypersensitivity have similar clinical, psychological, and functional profiles compared with patients with proven GERD and overlap with functional heartburn or reflux hypersensitivity overlap 29 …”
Section: Future Directionsmentioning
confidence: 99%